The Quest for Cellular Markers of HIV Reservoirs: Any Color You Like - Gilles Darcis; Gilles Darcis; Ben Berkhout; Alexander O. Pasternak (Frontiers in Immunology, 2019)
Combination antiretroviral therapy (ART) suppresses human immunodeficiency virus (HIV) replication and improves immune function, but is unable to eradicate the virus. Therefore, development of an HIV cure has become one of the main priorities of the HIV research field. The main obstacle for an HIV cure is the formation of latent viral reservoirs, where the virus is able to “hide” despite decades of therapy, just to reignite active replication once therapy is stopped. Revealing HIV hiding places is thus central to HIV cure research, but the absence of markers of these reservoir cells greatly complicates the search for a cure. Identification of one or several marker(s) of latently infected cells would represent a significant step forward toward a better description of the cell types involved and improved understanding of HIV latency. Moreover, it could provide a “handle” for selective therapeutic targeting of the reservoirs. A number of cellular markers of HIV reservoir have recently been proposed, including immune checkpoint molecules, CD2, and CD30. CD32a is perhaps the most promising of HIV reservoir markers as it is reported to be associated with a very prominent enrichment in HIV DNA, although this finding has been challenged. In this review, we provide an update on the current knowledge about HIV reservoir markers. We specifically highlight studies that characterized markers of persistently infected cells in the lymphoid tissues.